Preventing Parental Behavior Regarding Childhood Chewing Betel Habits In Preschool Children - Ngadilah, Christina; Eluama, Merniwati Sherly; Eky, Yansestina Erlince; Baunsele, Novianti (Universitas Islam Negeri Sumatera Utara, 2023)
In Nefoneke village, Kec. Takari District, Kupang, 79.5% of people consume betel nut, and they often teach their children to consume it in a unique way. A community service aims to increase the knowledge and attitude of preschool teachers, health cadres, and parents of preschool children about the dangers of betel nut consumption. The service involves collaborating with Posyandu cadres and mothers with children under five to socialize about the dangers of betel nut consumption, demonstrating proper tooth brushing, and creating booklets for distribution. Community education, cadre training, and mentoring are also provided to mothers to serve as role models for their children. Results show that 5 Family Welfare Education cadres, health cadres, and Early Education teachers have been trained in recognizing the dangers of betel nut consumption for pregnant women and children. The knowledge and attitudes of these cadres and teachers have increased from 50 to 80, and the